Progress in Propulsion Physics 2016
DOI: 10.1051/eucass/201608427
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics / Monte Carlo simulation of dusty gas flow in a “rotor-stator” set of airfoil cascades

Abstract: A dusty gas §ow through two, moving and immovable, cascades of airfoils (blades) is studied numerically. In the mathematical model of two-phase gas particle §ow, the carrier gas is treated as a continuum and it is described by the Navier Stokes equations (pseudo-DNS (direct numerical simulation) approach) or the Reynolds averaged Navier Stokes (RANS) equations (unsteady RANS approach) with the Menter k ω shear stress transport (SST) turbulence model. The governing equations in both cases are solved by computat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, several studies have shown some problems related to the effect of the turbulence on the colliding particles ( Berlemont et al, 1995;Sommerfeld, 2001;Berlemont et al, 2001;Wang et al, 2009;Pawar et al, 2014;Fede et al, 2015;He et al, 2015;Tsirkunov and Romanyuk, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown some problems related to the effect of the turbulence on the colliding particles ( Berlemont et al, 1995;Sommerfeld, 2001;Berlemont et al, 2001;Wang et al, 2009;Pawar et al, 2014;Fede et al, 2015;He et al, 2015;Tsirkunov and Romanyuk, 2016 ).…”
Section: Introductionmentioning
confidence: 99%